Numerical simulation of an RF asymmetric nonthermal plasma reactor used for plasma polymerisation - Elaissi, S; Alyousef, H (The International Journal of Multiphysics, 2019)
The aims of this paper is to investigate the control of plasma properties via the geometrical asymmetry effect in a capacitive coupled discharge used for polymer processing. The simulation results prove that the bulk position and density profiles of positive ions, negative ions, and electrons have a clear dependence on geometric asymmetry effect. The underlying mechanisms identified shows a more collisional sheath at the smaller powered surface due to the larger sheath width, and a higher energy at the smaller surface due to the higher mean sheath voltage compared to the larger surface. The argon modelling results are compared to experimental results from the literature for a range of operating conditions. The results show that the argon model results can be used to predict the plasma parameters for other gases used for polymer processing.